Incidence of depression and depressive symptoms and their predictive factors in community-dwelling older adults: a systematic review and meta-analysis protocol - Javier Jerez-Roig; Lízie Emanuelle Eulálio Brasileiro; Aílla Lorenna de Medeiros Paiva; Maria Yasmin Dantas de Medeiros; Dyego Leandro Bezerra de Souza (BMJ Open)
Introduction Faced with the continuous growth in the number of older people at a global level, some concerns are raised about the way people age. Health conditions such as depressive symptoms and depression have a direct or indirect impact on the quality of life of this population segment. The objective of this study is to verify the incidence of the various presentations of the depressive spectrum in the community-dwelling older population, as well as to analyse the predictive factors.Methods and analysis This systematic review and meta-analysis protocol follows the recommendation of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols. Searches will be conducted in PubMed, Web of Science, Scopus, Latin-American and Caribbean Literature on Health Sciences, Scientific Electronic Library Online and Cochrane databases, as well as grey literature. The search strategy involves terms related to ageing and the depressive spectrum found in observational studies. There will be no language restriction and the material included will be the ones whose publications took place until December 2020.Ethics and dissemination Formal ethical approval is not required on this research, since it only aims secondary data. After publishing the results in a scientifically supported journal, our findings may be disseminated to fill in the gaps and guide the production of more effective public policies directed at a more adequate care to the older population at a global level. The search process began in January 2021 and it is expected that all stages of the review will be completed by 30 November 2021.PROSPERO registration number CRD42019121616.